Editor's Note = Note du directeur [39, Spring 1997] - Iacovetta, Franca; Quinlan, Michael; Kealey, Gregory S. (Labour/Le Travail, 1997)
A letter to the editor is presented in response to the article "Immigration and Labour: Australia and Canada Compared" published in "Labour/Le Travail."
Keywords: LETTERS to the editor; Labor